Analisis Tartazin pada Makanan dan Minuman - Lina Nurfadhila; Marsah Rahmawati Utami; Elsya Martia; Dila Qhoirul Nisa; Regita Nailuvar (Jurnal Health Sains, 2023)
Additives that are often used in food and beverages with the aim of attracting the attention of consumers, namely commonly known as addictive substances in food and beverages, can be in the form of dyes, flavoring and aroma, enhancers, antioxidants, preservatives, emulsifiers, bleaches, thickeners and sweeteners. Tartrazine or FC&C Yellow 5 dye code E 102 is a synthetic dye that produces a lemon yellow color which is easily soluble in water, and is a derivative of coal tar which is a mixture of phenolic compounds, polycyclic and heterocyclic hydrocarbons. The tartrazine compound is resistant to light, acetic acid, HCl and 10% NaOH, while 30% NaOH will undergo a chemical reaction with a reddish color change. Easily faded in the presence of an oxidizing agent, FeSO4 will make the substance solution cloudy, whereas in the presence of copper (Cu) there will be a change from yellow to reddish. paper chromatography and Uv-Vis spectrophotometry methods were positive for containing Tartrazine dye with levels that exceeded the limit set by ADI (Acceptable Daily Intake), which is around 7.5 mg/Kg/day. Tartrazine dye levels in samples A, B, C, D and E respectively 1.06457 ; 28.1832 ; 40.6126 ; 15.7269 and 28.936 mg/L. The use of tartrazine that exceeds the maximum limit permitted by the Government can cause harmful effects to the health of the body. Among them such as causing urticaria (skin allergies), rhinitis (runny nose), asthma, purpura (bruises on the skin) and systemic anaphylaxis (shock). The maximum limit for the use of tartrazine coloring permitted by the Government of Indonesia based on BPOM Regulation Number 11 of 2019 states that the maximum level of use of tartrazine in food additives is a maximum of 100 mg/kg for confectionery or candy which includes hard and soft confectionery, nougat and others.